An estimated Hungarian method for data forwarding problem in underwater wireless sensor networks - Jing Wen; Dongwei Li; Linfeng Liu; Jiabin Yuan (International Journal of Distributed Sensor Networks)
With the increasing concern over marine applications in recent years, the technology of underwater wireless sensor networks has received considerable attention. In underwater wireless sensor networks, the gathered data are sent to terrestrial control center through multi-hops for further processing. Underwater wireless sensor networks usually consist of three types of nodes: ordinary nodes, anchor nodes, and sink nodes. The data messages are transferred from an ordinary node or an anchored node to one of the sink nodes by discrete hops. Data forwarding algorithms are at the core position of underwater wireless sensor networks, which determines data in what way to forward. However, the existing data forwarding algorithms all have problems that transmission delay is too high and delivery ratio is low. Thus, we propose a data forwarding algorithm based on estimated Hungarian method to improve delivery ratio and reduce transmission delay. The estimated Hungarian method is applied to solve the assignment problem in data forwarding process, where the anchor nodes receive the forwarding requests from ordinary nodes and optimize the waiting queue. By applying this method in underwater wireless sensor networks, data forwarding has great advantages in success rate and transmission delay, which has been validated by both analysis and simulation results.